Photoacoustic laser effects in live mouse blastocysts: pilot safety studies of DNA damage from photoacoustic imaging doses - Newcomer, Erin (F S Sci, 2020)
OBJECTIVES: To investigate the laser safety of photoacoustic imaging. In photoacoustic imaging, a pulsed laser of several nanoseconds is used to illuminate biological tissue, and photoacoustic waves generated by optical absorption are used to form images of the tissue. Photoacoustic imaging is emerging in clinical applications; however, its potential use in reproductive medicine has yet to be reported. DESIGN: Assessment of photoacoustic laser safety before its adoption by clinical reproductive medicine. SETTING: Academic medical center. ANIMALS: Blastocyst-stage mouse embryos. INTERVENTIONS: Potential DNA damage of photoacoustic laser exposure on preimplantation mouse blastocyst stage embryos was examined. Different embryos groups were exposed to either 5- or 10-minute 15-Hz laser doses (typical clinical doses) and 1-minute 1-kHz laser dose (significantly higher dose), respectively. MAIN OUTCOME MEASURES: A terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay was used to identify the rate of DNA damage in the laser-exposed blastocysts. RESULTS: The negative control blastocyst group (no laser exposure) had a mean of 10.7 TUNEL-positive nuclei. The 5- and 10-minute 15-Hz laser—exposed groups had a mean of 11.25 and 12.89 TUNEL-positive nuclei, respectively. The embryos exposed to the 1-kHz laser for 1 minute had an average mean of 12.0 TUNEL-positive nuclei. CONCLUSION: We demonstrated that typical lasers and exposure times used for photoacoustic imaging do not induce increased cell death in mouse blastocysts.